Absolute Mean Graceful Labeling in Various Graphs - V. J. Kaneria; H. P. Chudasama (International Journal of Mathematics And its Applications, 2017)
In the pesent study of paper, we defined absolute mean graceful labeling for various graphs. We proved all path graphs P_n, cycle C_n, complete bipartite graph K_m,n, grid graph P_m× P_n, step grid graph St_n and double step grid graph DSt_n are absolute mean graceful graphs.